Prognostic Significance of Age Within the Adolescent and Young Adult Acute Ischemic Stroke Population after Mechanical Thrombectomy: Insights from STAR - Lu, VM (2022)
Objective: Although younger adults have been shown to have better functional outcomes after mechanical thrombectomy (MT) for acute ischemic stroke (AIS), the significance of this relationship in the adolescent and young adult (AYA) population is not well defined given its undefined rarity. Correspondingly, the goal of this study was to determine the prognostic significance of age in this specific demographic following MT for large-vessel occlusions. Methods: A prospectively maintained international multi-institutional database, STAR (Stroke Thrombectomy and Aneurysm Registry), was reviewed for all patients aged 12-18 (adolescent) and 19-25 (young adult) years. Parameters were compared using chi-square and t-test analyses, and associations were interrogated using regression analyses. Results: Of 7192 patients in the registry, 41 (0.6%) satisfied all criteria, with a mean age of 19.7 ± 3.3 years. The majority were male (59%) and young adults (61%) versus adolescents (39%). The median prestroke modified Rankin Scale (mRS) score was 0 (range 0-2). Strokes were most common in the anterior circulation (88%), with the middle cerebral artery being the most common vessel (59%). The mean onset-to-groin puncture and groin puncture-to-reperfusion times were 327 ± 229 and 52 ± 42 minutes, respectively. The mean number of passes was 2.2 ± 1.2, with 61% of the cohort achieving successful reperfusion. There were only 3 (7%) cases of reocclusion. The median mRS score at 90 days was 2 (range 0-6). Between the adolescent and young adult subgroups, the median mRS score at last follow-up was statistically lower in the adolescent subgroup (1 vs 2, p = 0.03), and older age was significantly associated with a higher mRS at 90 days (coefficient 0.33, p < 0.01). Conclusions: Although rare, MT for AIS in the AYA demographic is both safe and effective. Even within this relatively young demographic, age remains significantly associated with improved functional outcomes. The implication of age-dependent stroke outcomes after MT within the AYA demographic needs greater validation to develop effective age-specific protocols for long-term care across both pediatric and adult centers.